73rd American Exhibition. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1979)
Asher, Michael ; Barry, Robert ; Graham, Dan ; Heizer, Michael ; Kawara, On ; LeWitt, Sol ; Martin, Agnes ; Nauman, Bruce ; Nordman, Maria ; Ruppersberg, Allen ; Ruscha, Edward ; Ryman, Robert ; Sandback, Fred ; Serra, Richard ; Stella, Frank ; Weiner, Lawrence
73rd American Exhibition, The Art Institute of Chicago, June 9 through August 5, 1979
boek